Optimization medium at the propagation and formation stage of micro tubers some varieties of potato - Nasution, Melvi Wahyu Angraini; Siregar, Lutfhi Aziz Mahmud; Basyuni, Mohammad (Talenta Publisher, 2025)
Potato cultivation in Indonesia is inadequate and experiences fluctuations. One of the obstacles is the limited availability of land for seed propagation and the high cost of in vitro media. The aim of this research is to increase the efficiency of MS media (Murashige and Skoog) for cultivating several potato varieties to form micro tubers in vitro. The research was conducted at the Biotechnology Laboratory, Faculty of Agriculture, USU Medan from June to November 2023. The research was carried out by planting node cuttings from four potato cultivars (Granola, Dayang Sumbi, Atlantic Malang, and Maglia) on MS medium with optimal concentration (1/2 MS, 3/4 MS, and 1 MS). This research uses two different stages: the propagation stage, namely shoot micropropagation, and the micro tuber creation stage. The results showed that the optimization of 3/4 MS media concentration showed quite good growth compared to 1/2 MS media concentration for growing potato explants in terms of the number of segments, number of leaves and number of primary roots. Furthermore, the optimization of media concentration and varieties did not show any significant influence or difference in the formation of micro tubers based on statistical tests.